Determinants of Intellectual Capital Performance of GCC Listed Banks - Al-Musali, Mahfoudh Abdul Karem (2013)
This study examines the level of intellectual capital (IC) performance of listed banks in the Arab Gulf Cooperation Council (GCC) countries using VAIC methodology and investigates the hypothesized impact of corporate governance variables (namely board diversity and ownership structure), bank specific characteristics (namely bank internationality, financial performance, bank adherence to Islamic Shariah principles, and bank risk), banking industry characteristics (namely banking industry concentration and presence of foreign banks) and macroeconomic environment on IC performance. In addition, this study determines the moderating role of the frequency of board meetings in the relationship between board diversity and IC performance. Multiple regression analyses are used to analyze the data. Hierarchical regression analysis is employed to examine if the frequency of board meetings moderates the relationship between board diversity and IC performance. The results of a survey of a sample of 128 GCC listed banks for the period 2008-2010, show that IC performance of GCC listed banks is low. Findings show that board interlocking, board size, representation of independent directors, family ownership, government ownership (when a government holds a majority of shares that is 51% or more), domestic strategic ownership, and domestic non-strategic ownership have significant relationships with IC performance. In addition, this study provides evidence that except for bank internationality, bank specific characteristics, banking industry characteristics, and macroeconomic environment play important roles in determining IC performance among GCC banks. Furthermore, the results generally do not support the study`s hypothesis that the impact of board diversity on IC performance is positive as the frequency of board meetings increases. The result of this study contributes to the body of knowledge in IC-related studies, particularly with regards to the determinants of IC performance. Findings provide some input to investors, managers, regulators and policymakers, as well as researchers in addressing the factors affecting IC performance.